Efficacy of quarantine treatments using reduced methyl bromide concentrations to disinfest Pinus radiata logs from New Zealand. (December 2020) - Najar-Rodriguez, Adriana J.; Hall, Matthew K.D.; Adlam, Anthony R.; Afsar, Saeedeh; Esfandi, Kambiz; Wilks, Catherine; Noakes, Emma; Clare, Graeme K.; Barrington, Anne; Brash, Don W.; Richards, Kate
Abstract: We report here the results of three successive toxicity studies against a selection of forest insect pests, conducted in New Zealand to determine the efficacy of reduced methyl bromide (MB) rates, i.e. rates lower than those currently used, to disinfest export pine logs. First, the relative tolerance to MB among the naked life stages of the golden-haired bark beetle, Hylurgus ligniperda, the black pine bark beetle, Hylastes ater (Coleoptera: Curculionidae) and burnt pine longhorn beetle, Arhopalus ferus (Coleoptera: Cerambycidae) was determined in the laboratory. Then, the most MB-tolerant species and life stage(s) in pine logs was subjected to selected fumigation schedules using reduced concentrations of MB. Finally, the results of the laboratory studies were validated under commercial conditions at the Port of Tauranga, New Zealand, using logs infested with the most tolerant life stage, and log stacks. Our results indicated that either 30 g/m 3 MB at >15 °C or 40 g/m 3 MB at ≤ 15 °C for 16 h would ensure quarantine security against forest insects in New Zealand export logs. These reduced MB concentrations are approximately 70% and 65%, respectively, lower than 80 g/m 3 at >15 °C or 120 g/m 3 at ≤15 °C. If implemented by regulatory agencies and accepted by trading partners, these concentrations will provide significant environmental and economic benefits to the New Zealand forest industry and will pave the way for other countries to implement similar approaches to reduce MB usage in accordance to the Montreal Protocol. Highlights: There is a continued pressure to reduce the volume of methyl bromide used for quarantine and pre-shipment (QPS) treatments. We investigated the feasibility of using reduced methyl bromide rates to fumigate export pine logs infested with key forest insect pests. Results showed that reductions of approximately 65–70% in methyl bromide use are feasible. These reductions will provide significant environmental and economic benefits to the New Zealand forest industry. They might also encourage other countries to implement similar approaches to reduce methyl bromide usage in accordance to the Montreal Protocol.